Smooth muscle contractile responses to bile acids in mouse ileum require TGR5 but not ASBT - Chang, Diana S.; Soni, Krishnakant G.; Preidis, Geoffrey A. (Frontiers in Neurology, 2024)
Background: Many disorders of gut-brain interaction (DGBIs) are more prevalent in women than men and feature alterations in gastrointestinal motility and bile acid homeostasis. Mechanisms by which bile acids regulate gastrointestinal motility are poorly characterized. We recently validated an adapted tissue bath technique using everted mouse ileum, which revealed differential contractile responses to ursodeoxycholic acid (UDCA) and deoxycholic acid (DCA). Here, we aimed to determine whether these responses are dependent on host sex, the plasma membrane bile acid receptor TGR5, or the apical sodium-dependent bile acid transporter ASBT. Methods: Ileal segments from male and female mice were everted and suspended in tissue baths. Contractile responses to physiologic concentrations of UDCA and DCA were quantified with or without TGR5 or ASBT inhibitors. Phosphorylation of extracellular signal-regulated kinase (ERK) and myosin light chain (MLC), markers of TGR5 activation and smooth muscle contraction, respectively, were assessed with western blot. Results: There were no sex differences in the dose-dependent contractile responses to bile acids. At 100 µmol/L, UDCA but not DCA increased MLC phosphorylation and increased contractility. TGR5 inhibition decreased ERK phosphorylation and led to decreases in contractility, phosphorylated MLC, and surprisingly, total MLC. ASBT inhibition did not affect contractile responses. Conclusions: Differential effects of UDCA and DCA on ileal smooth muscle contractility are not dependent on host sex or ASBT-mediated transport. Bile acids signal through mucosal TGR5, which regulates smooth muscle contractility by complex mechanisms. Understanding how bile acids differentially regulate gastrointestinal motility could facilitate new therapeutic options for specific DGBIs.